INNOVATIVE APPROACHES IN COACH EDUCATION PEDAGOGY - Morgan, Kevin; Jones, Robin L.; Gilbourne, David; Llewellyn, David (Nuances: estudos sobre Educação, 2013)
ABSTRACT: We know that coach education programmes continue to be criticized for their largely didactic methods of delivery and rather superficial engagement with the complex reality of practice and we understand that innovative approaches in coach education pedagogy means moving somewhat away from the competencies based approach and it has been increasingly argued that the aim of coach education should be to develop in practitioners a ‘quality of mind’ so that they are better equipped to deal with the problematic and dynamic nature of their work. The skills of coach educators in facilitating the learning of student coaches are crucial to the effectiveness of the pedagogies. Coach educators, therefore, must be committed to the approaches outlined in this article and invest the time and work necessary to learning new skills if they are to be successfully implemented. We found that teaching in this way resulted in a raised degree of responsibility on behalf of the tutors, not so much in relation to their content delivery, but for the subsequent student interaction and learning (JONES et al., 2011). In this sense tutors took greater care to listen and react to group interactions, recognising that their (non) interventions at (in) appropriate times could genuinely affect and frame ensuing students’ discussions and perceptions. A further area of research, therefore, could be to explore the issues surrounding the training and support of coach educators in implementing such pedagogical innovative approaches to coach education. RESUMO: Sabemos que os trabalhos de orientação de técnicos/professores são muito criticados por seus métodos pouco se aproximarem de práticas inovadoras. No entanto, práticas pedagógicas inovadoras devem se aproximar da realidade prática e avançar aos métodos tradicionais, considerando que uma pedagogia inovadora deve mover alguém do lugar onde se encontra para conhecer novas possibilidades. As habilidades dos técnicos/professores devem ser trabalhadas no sentido dos mesmos se constituírem facilitadores do processo de aprendizagem dos estudantes para se pensar numa pedagogia inovadora. Entendemos que uma concepção pedagógica construída nessa direção possibilita o desenvolvimento tanto de técnicos/professores, assim como os estudantes e pesquisas educacionais devem caminhar nessa direção, tendo em vista a necessidade de transformação qualitativa dessa áreade atuação.http://dx.doi.org/10.14572/nuances.v24i1.2170